A Novel Use of Early Radiation Therapy in the Treatment of Hyperbilirubinemia in a Patient with Primary Hepatic Lymphoma and Chronic Hepatitis C - Venkata S. Tammana; Rehana Begum; Patricia Oneal; Hemamalini Karpurapu; Amruta Muley; Sri Lakshmi Hyndavi Yeruva; Jacquelyn Dunmore-Griffith; Eyasu Mekonen; Nabhani Hasan (Case Reports in Gastrointestinal Medicine)
Lymphomas arising in the liver are extremely rare. Here, we describe a case of Hepatitis C virus infection with primary hepatic lymphoma (PHL) presenting with hyperbilirubinemia. A 45-year-old African American male presented with abdominal pain, pruritus, and itching for two days. CT of abdomen and pelvis with contrast showed numerous masses in the liver. The liver biopsy was consistent with diffuse large B cell lymphoma (DLBCL). Conventional chemotherapy was avoided initially because of hyperbilirubinemia. Hence, radiation therapy was given initially to reduce his bilirubin levels and tumor size. The patient was able to complete six cycles of rituximab combined with cyclophosphamide, adriamycin, vincristine, and prednisone (R-CHOP) chemotherapy and achieved a complete response verified by positron emission tomography-computed tomography (PET-CT). PHL should be considered when there are numerous space occupying liver lesions seen on imaging. Hyperbilirubinemia may be a reason for delay in treatment for some of these patients. Hence, the role of radiation therapy prior to treatment with R-CHOP is an alternative to management for stage IV diffuse large B cell lymphoma.